SILDENAFIL ALLEVIATES INSULIN SENSITIVITY VIA ATTENUATING OXIDATIVE STRESS AND PROINFLAMMATORY CYTOKINE PRODUCTION IN DIABETIC RATS - N B S ABORYAG; A M MAHMOUD; S A RAMADAN (International Journal of Pharma and Bio Sciences, 2013)
The present study was hypothesized to assess the effect of sildenafil, a phosphodiesterase inhibitor, on proinflammatory cytokines and hyperglycemia-mediated oxidative stress in type 2 diabetic rats. Diabetes was induced by feeding rats with high fat diet for 2 weeks followed by an intraperitoneal injection of streptozotocin. In the diabetic control group, levels of glucose were significantly increased, while serum insulin level was decreased. In addition, serum TNF-α, IL-6, IL-1β, total cholesterol, triglycerides, LDL-cholesterol and vLDL-cholesterol were significantly elevated in diabetic rats. Moreover, hepatic MDA was significantly increased in diabetic rats, while GSH content as well as GPx and SOD activities were significantly decreased. Both doses of sildenafil alleviated the altered parameters. Collectively, sildenafil exerts protection to type 2 diabetic rats by alleviating insulin sensitivity, potentiating the antioxidant defense system and suppressing proinflammatory cytokine production.